FINANCIAL SUPPORT OF SMALL AND MEDIUM BUSINESS IN UKRAINE - Mykhailiv , G.V. (The actual problems of regional economy development, 2019)
In the current conditions of intensive development of the national economy, the functioning of small business is of great importance, which significantly influences the development of the domestic economy, The article deals with economic essence of small business, it justifies the forms and methods of microcredit of small enterprises and also considers the international experience of financial provision of microcredit. The main purpose of this article is justification of the recommendations as for creation of system of financial provision of development of small and medium-sized businesses. The actual state of the development and functioning of small and medium business in Ukraine, forms and methods of financial provision is analyzed and the criteria and factors affecting the development of small enterprise structures are determined. The actuality of the issues raised in this article is reinforced by the fact that the slowness and inconsistency of the movement of Ukraine towards market reforms is largely due to this underestimation of the role and importance of small and medium businesses as the structure forming element of the market economy. There are a number of adverse factors in Ukraine that make it difficult to financing of business activity. In the research process the problems and outlined the prospects of financial support of small business development at local and regional levels are identified. The proposals of priority measures for effective financial support and the main perspectives of financial support for the development of small and medium-sized businesses are justified.